THE SUCCESS OF ORGANIC AGRICULTURE AND ITS IMPLICATIONS FOR FOOD SECURITY: A REVIEW OF MODERN LITERATURE - Rita Hayati; Loso Judijanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This paper explores the success of organic farming and its impact on food security through an analysis of modern literature. Organic farming has been shown to provide significant benefits for environmental sustainability, such as increased biodiversity and soil health, as well as agricultural products with higher nutritional quality. However, challenges to meeting global food demand remain, mainly due to lower yields compared to conventional methods and high production costs. Modern literacy suggests the need for technological support and more active government policies to overcome these obstacles. With the right support, organic farming can strengthen the global food system to be more resilient to climate change, overall strengthening food security for future generations.